Orthodontic Knowledge and Awareness among Medical Students of a Tertiary Medical College - Shrestha, Natasha; Shrestha, Kaschev (Journal of College of Medical Sciences-Nepal, 2024)
Background Orthodontics, a vital branch of dentistry dedicated to correcting malalignment and malocclusion, stands as a prime example of such a specialty that frequently finds itself overlooked within the medical community. This study aims to evaluate the levels of orthodontics knowledge and awareness of medical faculty students and future medical doctors. Methods A cross-sectional study was conducted among 296 students of College of Medical Sciences and Teaching Hospital from January 2024 to May 2024. Ethical approval was taken from Institutional Review Committee of College of Medical Sciences. Then data was entered in Excel and data was analyzed by using SPSS 18. Data was analyzed by using descriptive and inferential statistical tools. p-values less than 0.05 were considered as statistically significant. Results This research was conducted among 41.6% female and 58.4% were male. This research showed that 62.2% respondents had good knowledge and awareness of orthodontic (with 95% CI 56.67% to 67.73%). Also, 65.9% female and 59.5% male had good knowledge and awareness on orthodontic likewise, 66% clinical and from pre-clinical side 58.5% had good level of knowledge and awareness on orthodontic. This research showed that there is no association between gender and level of knowledge and awareness (p-value>0.05). Conclusions This research showed that more than sixty percentage respondents had good knowledge on orthodontics likewise more than ninety percentage respondents know the meaning of orthodontics.